YOGA anytime, anyplace, anybody
There are many advantages of yoga but the most compelling reason for practising it is also the most simple: it makes you feel great.Starting with short duration programmes,this book progressivelytakes you to medium and long duration routines that will providegreat benefits. Whats more, these routines are designed in such away that you fit yo into your life rather than fit your life aroundyoga. Along with accompanying photographs (with and without props)at every step,every programme concludes with a quick reminder panelto help you remember the key postures in the correct sequence.Knowing that yoga can contribute in many ways to attain ahealthy mind and a healthy body, this book can teach you how tomobilise the joints of the body, improve flexibility and becomemore self-reliant physically; and is must-have for both beginnersand regular practitioners.